Effect of nanoparticle density on the kinetics of SPP-assisted plasmonic assembly - Kethahalli Shivappa Mahadeva Prasad; Rajeev K. Sinha; Aswini Kumar Mohapatra; Aseefhali Bankapur (Scientific Reports)
Abstract The dynamic assembly of plasmonic metal nanoparticles (PMNPs) in an aqueous medium as a Surface-enhanced Raman spectroscopy (SERS) substrate offers advantages for analyzing liquid samples, as it generates 3-dimensional intraparticle hotspots. The surface plasmon polariton (SPP) assisted surfactant-free reversible assembly of plasmonic nanoparticles (NPs) is one of the latest methods, and it stands as a promising approach for conducting SERS measurements on molecules that demand a physiological environment. However, the assembly process is dynamic and requires a thorough analysis of the behavior of NPs in the combined forces of fluid convection and plasmonics. This study investigates the kinetics of the plasmonic assembly of gold nanoparticles (AuNPs) and the influence of NP density through microscopy and SERS monitoring over 60 min. The study reveals that the assembly size and density grow gradually at an NP density-dependent rate. The SERS intensity of the analyte molecules increases rapidly and begins to decrease gradually after reaching a maximum value at an assembly time that is NP density-dependent. The assembly time at maximum SERS intensity is found to be inversely proportional to the NP density. Notably, when SERS intensity is maximum, the assembly radius remains constant at 119±1 μm for all the NP densities.